Enterprise risk management : a manager's journey - Pickett, K. H. Spencer (Hoboken, N.J. : Wiley, 2006)
Enterprise Risk Management creates an awareness of ERM and how risk may be managed across all parts of the business to promote organizational success. The book includes diagrams and checklists and follows a "how-to" format that can be used by managers to ensure they understand and can help develop a good ERM process
Enterprise Risk Management: A Manager's Journey; CONTENTS; PROLOGUE; Chapter 1: A NEW JOURNEY; Chapter 2: JETTING OFF; Chapter 3: THE WARMUP; Chapter 4: THE CONFERENCE DAY; Chapter 5: CONFERENCE SESSION ONE; Chapter 6: CONFERENCE SESSION TWO; Chapter 7: CONFERENCE SESSION THREE; Chapter 8: CONFERENCE SESSION FOUR; Chapter 9: CONFERENCE SESSION FIVE; Chapter 10: CONFERENCE SESSION SIX; Chapter 11: CONFERENCE SESSION SEVEN; Chapter 12: CONFERENCE SESSION EIGHT; Chapter 13: CONFERENCE SESSION NINE; Chapter 14: CONFERENCE SESSION TEN; Chapter 15: CONFERENCE SESSION ELEVEN.
Includes index.
Print version record.
English.
John Wiley and Sons
Keywords: Risk management; Gestion du risque; risk management; BUSINESS & ECONOMICS -- Insurance -- Risk Assessment & Management; Risk management